Sexual Assaults, Bad Hookups, and Bad Dates: Comparisons of the Contextual Features Among College Women’s Hypothetical and Real-Life Sexual and Dating Experiences - Sheffield, Alexis (Journal of interpersonal violence, 2023)
Two hundred forty-seven (N = 247) undergraduate women at a medium-sized, Southwestern university provided written descriptions of a hypothetical sexual assault (SA). Women with a prior history of SA also described their actual SA experiences; women without a SA history provided a written description of a prior bad date or hookup. The contextual features of SA scripts were compared to those of actual SA experiences. Several characteristics of a stereotypical or “blitz rape” (e.g., physical force by a stranger) were more likely to be included in SA scripts relative to women’s actual SA experiences. Victimized women were also more likely to include verbal coercion, a hangout/hookup context, and previous consensual kissing in their SA experiences, in comparison to their SA scripts. The contextual features of SA experiences were also compared to the contextual features of bad dates or bad hookups. SA experiences, relative to bad dates, were more likely to include alcohol use, physical and verbal coercion by the perpetrator, and passive resistance. SA experiences, relative to bad hookups, were more likely to include physical and verbal coercion by the perpetrator, and knowing the man for less than 1 week. Victimized participants SA experiences were also found to be less likely to include previous consensual kissing and consensual intercourse in comparison to bad hookup experiences of nonvictimized women. Overall, there was considerable overlap between the contextual features present across all experiences. The lack of differentiation among these events may explain why women experience difficulty acknowledging whether they have experienced SA.